2013
DOI: 10.1186/1866-1955-5-24
|View full text |Cite
|
Sign up to set email alerts
|

Resting state EEG abnormalities in autism spectrum disorders

Abstract: Autism spectrum disorders (ASD) are a group of complex and heterogeneous developmental disorders involving multiple neural system dysfunctions. In an effort to understand neurophysiological substrates, identify etiopathophysiologically distinct subgroups of patients, and track outcomes of novel treatments with translational biomarkers, EEG (electroencephalography) studies offer a promising research strategy in ASD. Resting-state EEG studies of ASD suggest a U-shaped profile of electrophysiological power altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
340
2
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(381 citation statements)
references
References 163 publications
(233 reference statements)
28
340
2
11
Order By: Relevance
“…The baseline decreased resting state a power was consistent with other EEG studies in ASD. 25,26 Moreover, a role for a frequency band oscillations has been shown in specific cognitive mechanisms. 27 The increase in the a frequency power after treatment may be an underlying mechanism of patient's improvement in cognition and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The baseline decreased resting state a power was consistent with other EEG studies in ASD. 25,26 Moreover, a role for a frequency band oscillations has been shown in specific cognitive mechanisms. 27 The increase in the a frequency power after treatment may be an underlying mechanism of patient's improvement in cognition and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing neural activity can be assessed noninvasively during a resting-state EEG recording, i.e., in the absence of task performance or sensory stimulation, in which patterns of neural oscillations may be detected [2]. It has been suggested that elevated oscillatory activity in ASD might indicate hyperactivity in cortical circuits, and subsequently may be associated with the ''autistic'' state [3,4], which is in agreement with a recent review summarizing EEG abnormalities during resting-state paradigms in ASD, reporting increased power in low (delta, theta) and high frequencies (beta, gamma) and reduced activity in middlerange frequencies (alpha) [2]. A few experimental studies report altered resting-state gamma activity by EEG or MEG.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, alterations in gamma power have been Identified among other disorders that share some, but not all features of schizophrenia. Specifically, people with autism spectrum disorders (ASD) also display increased background gamma power, but do not experience hallucinations and delusions (Wang et al, 2013;van Diessen et al, 2014). We propose that the developmental timing during which increased background activity emerges determines the types of subjective and functional abnormalities that result.…”
Section: Discussionmentioning
confidence: 99%